Many stones - Coman, Carolyn (New York, N. Y. bPuffin Books, 2000)
A 2000 National Book Award finalist. -- A 2001 Michael L. Printz Honor Book
Keywords: Death -- Fiction; Family life -- Fiction; South Africa -- Fiction